In vitro antimicrobial activity of flowering and non-flowering ocimum graveolens methanol extracts (Tanzania Medical Journal, 2015)
Objective: To screen for in vitro antimicrobial activity of methanolic extracts of flowering and non-flowering parts of Ocimum graveolens. Methods: The methanolic extracts of flowering and non-flowering parts of the plant were dissolved in 5% dimethylsulfoxide and serially diluted to concentrations of 0.03-64.0mg/ml. The microdilution with modified [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide]–(MTT) method was used for evaluation of antibacterial activity on four strains of reference microbes namely Pseudomonas aeruginosa, Escherichia coli, Candida albicans and Staphylococcus aureus. A 30:1 ratio of culture medium/broth and sensitized microbial suspension with were added to each well. The microplates were aerobically incubated overnight at 37ºC. Five microlitres of MTT was added to each well and incubated for 4 hours prior to spectrophotometric determination of enzymatically converted MTT’s by-products (formazan, a purple/blue precipitate) at 550nm. Inhibition percentage of the extracts and antibiotics was determined by comparison with negative controls (untreated wells). Results: The antimicrobial effect of the extracts of non-flowering parts of O. graveolens exhibited a negative correlation with the extracts’ concentrations (r = -0.915, p = 0.01). The lowest and highest percentage inhibition for non-flowering methanolic was -62.3% and 38.2% on C. albicansand Pseudomonas spp respectively, at 64mg/ml which is the highest assayed extract’s concentration. The methanolic extract of flowering plant showed a positive correlation between extract’s concentrations and percentage inhibition (r =0.313, p= 0.005). The flowering plant extract exerted the highest mean inhibition of 98.06±2.17% (E. coli) and the least 91.04±7.13% (P. aeruginosa) at concentrations of 0.5-8.0mg/ml. The mean inhibition rates of the flowering extracts were comparable to that of control antibiotics: 71.70-100% and 73.9-100% respectively (p<0.05). The enzymatically formed formazan was detectable up to concentrations of 8.0mg/ml for flowering and more than 64mg/ml for non-flowering extracts, and up to 0.25 mg/ml for antibiotics. Conclusion: Methanolic extract of the flowering O. graveolens exhibited pronounced antimicrobial activity when compared with the positive controls and unlike the non-flowering extracts. Results obtained from the flowering O. graveolens plant can justify its traditional use for treatment of common disease conditions. However, further studies should be conducted to buttress these findings and isolation of active antimicrobial components.